Activation of Complement Components on Circulating Blood Monocytes From COVID-19 Patients - Lage, Silvia Lucena; Rocco, Joseph M.; Laidlaw, Elizabeth; Rupert, Adam; Galindo, Frances; Kellogg, Anela; Kumar, Princy; Poon, Rita; Wortmann, Glenn W.; Lisco, Andrea; Manion, Maura; Sereti, Irini (Frontiers in Immunology, 2022)
The coronavirus disease-2019 (COVID-19) caused by the SARS-CoV-2 virus may vary from asymptomatic to severe infection with multi-organ failure and death. Increased levels of circulating complement biomarkers have been implicated in COVID-19-related hyperinflammation and coagulopathy. We characterized systemic complement activation at a cellular level in 49-patients with COVID-19. We found increases of the classical complement sentinel C1q and the downstream C3 component on circulating blood monocytes from COVID-19 patients when compared to healthy controls (HCs). Interestingly, the cell surface-bound complement inhibitor CD55 was also upregulated in COVID-19 patient monocytes in comparison with HC cells. Monocyte membrane-bound C1q, C3 and CD55 levels were associated with plasma inflammatory markers such as CRP and serum amyloid A during acute infection. Membrane-bounds C1q and C3 remained elevated even after a short recovery period. These results highlight systemic monocyte-associated complement activation over a broad range of COVID-19 disease severities, with a compensatory upregulation of CD55. Further evaluation of complement and its interaction with myeloid cells at the membrane level could improve understanding of its role in COVID-19 pathogenesis.